2016
DOI: 10.1007/s11892-016-0799-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Atherosclerosis in Diabetes: Current State

Abstract: (310) 222-4107 mbudoff@labiomed.org Fax (310) 782-9652This work was supported and funded by American Diabetes Association (ADA) with grant reference of 7-12-CT-08. 1 AbstractPrevalence of diabetes mellitus is rapidly increasing worldwide. Disease is an independent and important risk factor for cardiovascular disease in both men and women. Cardiovascular events including myocardial infarction and stroke are the primary causes of mortality in both type 1 and type 2 diabetes. Affected patients frequently have asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
9
0
2
Order By: Relevance
“…Long-term increased hyperglycemia damages the vascular endothelial cells, promotes the migration and proliferation of vascular smooth muscle cells ( 11 ), and activates plasminogen activator inhibitor-1 in the body ( 12 ), thus increasing the levels of procoagulant factors as well as antithrombotic factors ( 13 ) accelerating the formation of thrombosis and the incidence of cardiovascular events in patients with T2DM complicated with CHD ( 14 ). In addition, in patients with T2DM complicated with CHD ( 15 ), the body's inflammatory cytokines and their effector cells will lead to cytotoxicity inducing pancreatic β-cell apoptosis, thereby increasing insulin resistance ( 16 ). This will, in turn, induce the adipose tissue cells to secrete more inflammatory factors ( 17 ), further aggravating the body's inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term increased hyperglycemia damages the vascular endothelial cells, promotes the migration and proliferation of vascular smooth muscle cells ( 11 ), and activates plasminogen activator inhibitor-1 in the body ( 12 ), thus increasing the levels of procoagulant factors as well as antithrombotic factors ( 13 ) accelerating the formation of thrombosis and the incidence of cardiovascular events in patients with T2DM complicated with CHD ( 14 ). In addition, in patients with T2DM complicated with CHD ( 15 ), the body's inflammatory cytokines and their effector cells will lead to cytotoxicity inducing pancreatic β-cell apoptosis, thereby increasing insulin resistance ( 16 ). This will, in turn, induce the adipose tissue cells to secrete more inflammatory factors ( 17 ), further aggravating the body's inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The MESA [23] and Heinz Nixdorf [24] studies demonstrated that CAC is a predictor of coronary events and is useful for stratification of cardiovascular risk among patients in primary prevention. This is also true for patients with diabetes: the higher the CAC score, the higher the risk of cardiovascular events in subjects with diabetes [25]. …”
Section: Module 2: Screening Of Subclinical Atherosclerosismentioning
confidence: 99%
“…In recent years, the prevalence of diabetes mellitus showed a continuous increase in the trend worldwide [1]. Simultaneously, diabetes mellitus remains a significant independent cardiovascular risk factor.…”
Section: Introductionmentioning
confidence: 99%